(untitled) - Ponniah, Paulraj (New Jersey, 2003)
Unlike other IT resources currently available that tend to focus on a particular product, Database Design and Development: An Essential Guide for IT Professionals was created to give today's IT directors and other IT staff a solid basic knowledge of database design and development to help them make educated decisions about the right database environment for their companies. Today's IT professionals must understand the fundamentals in order to determine their next steps for specializing in the vast field of database technology.
Keywords: Database design,Database management,Thiết kế cơ sở dữ liệu,Quản trị cơ sở dữ liệu